A Compassionate Framework for Reducing Harm in Public Health Higher Education: Implications for the COVID-19 Pandemic. (March 2021) - Burke, Jessica G.; Egan, James E.; Coulter, Robert W. S.; Mitchell, Shannon; Olaniyan, Abisola; Hawk, Mary
We believe a harm reduction framework offers guidance for managing the student-teacher relationship in pandemic situations. This commentary defines the six principles of harm reduction (humanism, pragmatism, individualism, autonomy, incrementalism, and accountability without termination) and describes how these principles can be applied within the public health higher educational system in the COVID-19 era. The key points are intended to stimulate thought and discussion about how to balance general uncertainty, concerns about what is best for population and personal health, the tensions between collectivism and individualism, and our commitment to training and protecting the health of the next generation of public health professionals. We recommend that educators, in public health and other higher education settings, use the harm reduction principles to guide their interactions with students and to build more compassionate and collectivist communities that allow people to learn and thrive.